(3GdGfJNGH GdbQjH ef GdJbQjHs - (3GdYGedj GdCUagGfj GdcGXej, CHh eMeO, MSf Hf gGOj Hf eMeO Ydj, J (B1354(3g`s ((3eTgO CejQ GdeDefjf Ydj Hf CHj WGdHs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg QSGdI GSJNQLJ ajgG eG Qhi Yfg YdeGA Cgd GdSfI ef GdTjYI hUQMhG HJTjYg Ch QGaVjJg eY Pdc eY GdOdGdI Ydi ef CNQL GdMOj hGdLGeY GdPj CNQL ajg (B...s
(3BNQgG (B:s
... (3HGH Gdcfi CHh MQH GHf CHj GdCShO GdODdj GdHUQj KbI bjd GSeg eMLf hbjd YWGA ef GdKGdKI eGJ SfI KeGf heGFI CNQL dg Y , CHh MeRI GdoqKeGdj HVe GdeKdKI hJNaja Gdeje GSeg KGHJ Hf Uajg (B. (3Jes
(3efShNI Yf fSNI efShNI Yf fSNI efShNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/224s
(3GdPQjYI (B2 - 202 ( 1449 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs